Dari FOMO Menuju Pemanfaatan Media Digital yang Produktif: Edukasi Kewirausahaan Digital Berbasis Nilai-nilai Islam bagi Siswa SMA: From FOMO to Productive Digital Engagement: An Islamic Values–Based Digital Entrepreneurship Education Program for High School Students - Norhaedah K; Ernawati Ernawati; Suci Susilawaty Muchtar; Ahmad Syidqi Ramadan; Natasya Putri (FAI UIM, 2026)
The rapid expansion of digital technology has intensified the phenomenon of Fear of Missing Out (FOMO) among adolescents, often encouraging patterns of social media use that are more consumptive than productive. At the same time, most digital entrepreneurship education initiatives continue to emphasize business competencies while giving limited attention to the ethical foundations needed to guide responsible digital engagement. This community engagement program was designed to enhance digital entrepreneurship literacy among high school students by integrating Islamic values into entrepreneurship education, enabling participants to transform digital trends into productive, creative, and ethically responsible business opportunities. The program was implemented at SMAN 18 Makassar and involved 45 eleventh-grade students. It adopted a participatory learning approach combined with experiential learning. Program activities included needs assessment, interactive lectures, group discussions, guided development of digital business ideas grounded in Islamic values, and evaluation through observation, reflective discussion, and questionnaires. The findings indicate substantial improvements across all measured dimensions of digital entrepreneurship literacy, including understanding of digital business opportunities, social media marketing, Islamic business ethics, the ability to identify entrepreneurial opportunities, and entrepreneurial motivation. The program also shifted participants' perspectives from passive and consumption-oriented engagement associated with FOMO toward a more productive use of digital media while strengthening their understanding of ethical business practices rooted in Islamic principles. This program contributes an integrated community engagement model that combines digital literacy, entrepreneurship education, and Islamic character formation, offering a practical framework for cultivating ethically grounded digital entrepreneurs among secondary school students.